2023
DOI: 10.3390/microorganisms11051339
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic Hemorrhagic Disease Virus: Current Knowledge and Emerging Perspectives

Abstract: Epizootic Hemorrhagic Disease (EHD) of ruminants is a viral pathology that has significant welfare, social, and economic implications. The causative agent, epizootic hemorrhagic disease virus (EHDV), belongs to the Orbivirus genus and leads to significant regional disease outbreaks among livestock and wildlife in North America, Asia, Africa, and Oceania, causing significant morbidity and mortality. During the past decade, this viral disease has become a real threat for countries of the Mediterranean basin, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 169 publications
0
21
0
Order By: Relevance
“…The occurrence, prevalence, and geographical distribution of this disease are intricately linked to the species and geographical spread of its primary transmission vector, Culicoides [ 3 ]. Current research highlights C. obsoletus , C. actoni , C. brevitarsis , C. imicola , and C. oxystoma as the primary vectors or potential carriers of EHDV [ 38 , 39 ]. In this study, two strains of EHDV-10 were successfully isolated from C. tainanus collected from cattle pens in Jiangcheng.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence, prevalence, and geographical distribution of this disease are intricately linked to the species and geographical spread of its primary transmission vector, Culicoides [ 3 ]. Current research highlights C. obsoletus , C. actoni , C. brevitarsis , C. imicola , and C. oxystoma as the primary vectors or potential carriers of EHDV [ 38 , 39 ]. In this study, two strains of EHDV-10 were successfully isolated from C. tainanus collected from cattle pens in Jiangcheng.…”
Section: Discussionmentioning
confidence: 99%
“…EHD is a global concern, with notable regions of prevalence spanning North America, Africa, Australia, and Asia [ 29 ]. In recent times, this disease has extended its reach into the Mediterranean Basin, affecting countries like Morocco, Algeria, Tunisia, Israel, Jordan, and Turkey [ 38 ]. This expansion demonstrates that EHDV has not only established a wide geographical presence but continues to broaden its scope.…”
Section: Discussionmentioning
confidence: 99%
“…Like BTV, the primary determinant of serotype specificity is the outer capsid VP2 protein [7]. There are seven officially determined serotypes [8] and at least three putative strains representing new EHDV serotypes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the virus has also been detected in Canada and Mexico, as well as in other parts of the world: South America, Africa, the Middle East, Japan, Southeast Asia, and Australia [ 3 ]. To date, seven serotypes of EHDV have been reported, named 1–2 and 4–8, which were identified based on phylogenetic studies, sequencing data, and cross-neutralization assays [ 4 ]. Genetic analyses demonstrated that the previously identified serotype 3 (Nigerian strain IbAr 22619) was serotype 1 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%